2018
DOI: 10.1111/rec.12896
|View full text |Cite
|
Sign up to set email alerts
|

A cultural approach to wetlands restoration to assess its public acceptance

Abstract: Ecological restoration (ER) of coastal wetlands is extremely important because they provide a huge variety of ecosystem services (ES), but they are the most degraded ecosystems in the world. However, coastal wetlands are usually located in largely modified and densely populated landscapes. Hence their restoration may conflict with cultural values. Therefore, considering the cultural dimension of ER is a way of increasing public acceptance of restoration projects. In this study, we assessed the public acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Ongoing efforts at collecting evidence of NbS effectiveness are well-positioned to increase public acceptance (Davis and Naumann 2017;Faivre et al, 2018;Chausson et al, 2020). However, perhaps the most powerful way to provide such evidence is through participatory citizen science initiatives in which residents can see for themselves the positive results of the NbS (Holstead et al, 2017)-not just risk reduction but also, e.g., biodiversity gains (Davenport et al, 2010;Pueyo-Ros et al, 2019). Findings show a very high willingness to actively engage in the NbS projects.…”
Section: Key Themes and Recommendations For Increasing Public Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing efforts at collecting evidence of NbS effectiveness are well-positioned to increase public acceptance (Davis and Naumann 2017;Faivre et al, 2018;Chausson et al, 2020). However, perhaps the most powerful way to provide such evidence is through participatory citizen science initiatives in which residents can see for themselves the positive results of the NbS (Holstead et al, 2017)-not just risk reduction but also, e.g., biodiversity gains (Davenport et al, 2010;Pueyo-Ros et al, 2019). Findings show a very high willingness to actively engage in the NbS projects.…”
Section: Key Themes and Recommendations For Increasing Public Acceptancementioning
confidence: 99%
“…Lastly, whether NbS are seen to enhance or degrade local history, identity, and place can influence the degree of public acceptance (Buijs 2009;Bihari and Ryan 2012;Roca and Villares 2012;Brink and Wamsler 2019). Individuals' connectedness to place may determine whether shifts away from the status quo or the idealized environment face opposition (Buijs 2009;Jacobs and Buijs 2011;Pueyo-Ros et al, 2019) or if NbS that enhance local values find support (Schmidt et al, 2014;Brink and Wamsler 2019). Recent literature reviews on the subject have also found risk, nature, and place to be key themes of variables that influence perceptions of NbS across diverse geographic and hazard contexts (Han and Kuhlicke 2019;Anderson and Renaud 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst some authors suggest that restoration work and communication efforts do not always consider the cultural services provided by wetlands (Davenport et al 2010;Pueyo-Ros, Ribas, and Fraguell 2019), there is little reference to physical cultural heritage or forms of intangible heritage such as folklore, art and customs, in published studies on perceptions of wetlands. Where cultural values are considered these tend to dwell on recreation, aesthetic appeal (e.g.…”
Section: Public Perceptions Of Wetlands and Peatlandsmentioning
confidence: 99%
“…Dobbie 2013; Lee 2017), tourism and, less frequently, a sense of calm or tranquillity. These aspects may be overemphasised as they are the simplest to measure, or reflect a focus on economically valued cultural services (Davenport et al 2010;Pueyo-Ros, Ribas, and Fraguell 2019).…”
Section: Public Perceptions Of Wetlands and Peatlandsmentioning
confidence: 99%
“…Support is shown for both NbS and grey measures that help preserve place (Chowdhury 2002 ; de Groot and de Groot 2009 ; Bihari and Ryan 2012 ), while strong opposition is shown to measures that shift from the status quo or the idealized environment (Roca and Villares 2012 ). In the context of NbS, Goeldner-Gianella et al ( 2015 ) and Pueyo-Ros et al ( 2018 ) describe a high degree of local attachment to coastal promenades under threat from depolderization and wetland restoration, respectively. Measures are opposed among residents with higher place attachment due to changes in place and services, despite the fact that a wilder coastline would provide overall greater benefits to a broader swath of society.…”
Section: Resultsmentioning
confidence: 99%